Consider $(1)$

$$\sum_{n=0}^{\infty}\left(-{1\over x}\right)^n\cdot{\Gamma\left({2n+1\over 2}\right)\over n!}=S\tag1$$ $x>0$

How does one show that $S=\sqrt{{x\pi\over x+1}}$

An attempt:

$$\Gamma\left({1\over 2}+n\right)={(2n-1)!!\sqrt{\pi}\over 2^n}$$

$(1)$ becomes

$$\sum_{n=0}^{\infty}\left(-{1\over x}\right)^n\cdot{(2n-1)!!\over 2^n}\cdot{1\over n!}=\sqrt{x\over x+1}\tag2$$

further to

$$\sum_{n=0}^{\infty}\left(-{1\over x}\right)^n\cdot{1\over 2^n(2n-2)!!}=\sqrt{x\over x+1}\tag3$$


We wish to calculate ($x>1$)

$$ S=\sum_{n\geq0}\frac{(-1/x)^n}{n!}\Gamma(n+1/2) $$

we have that $\Gamma(n+1/2)=\int_0^{\infty} t^{n-1/2}e^{-t}dt$


$$ S=\int_0^{\infty}dte^{-t}t^{-1/2}\sum_{n\geq 0}\frac{(-t/x)^n}{n!}=\int_0^{\infty}dte^{-t(1+1/x)}t^{-1/2}=\frac{\sqrt{\pi x}}{\sqrt{1+x}} $$

the interchange of sum and integral is justified since $\int_0^{\infty}e^{-t}t^z$ converges absolutly for any $z>-1$ and the last integral can be turned into a simple Gaussian one via $t\rightarrow t^2$

note the non obvious limit $\lim_{x\rightarrow\infty} S(x)=\sqrt{\pi}$

  • 1
    $\begingroup$ Succinct and complete! Well done. (+1) $\endgroup$ – Mark Viola Feb 15 '17 at 21:44
  • $\begingroup$ "Succinct" i learned a new english word...thanks! $\endgroup$ – tired Feb 15 '17 at 21:46
  • $\begingroup$ .... Prego! ... $\endgroup$ – Mark Viola Feb 15 '17 at 21:49
  • 1
    $\begingroup$ Great approach! $\endgroup$ – Ron Gordon Feb 15 '17 at 21:51

We note that

$$\frac{\Gamma \left ( n+\frac12 \right )}{\Gamma \left ( n+1 \right )} = \frac1{\sqrt{\pi}} \int_0^1 dy \, y^{-1/2} (1-y)^{n-1/2} $$


$$\begin{align}\sum_{n=0}^{\infty} \frac{\Gamma \left ( n+\frac12 \right )}{\Gamma \left ( n+1 \right )} w^n &= \frac1{\sqrt{\pi}} \int_0^1 dy \, y^{-1/2} (1-y)^{-1/2} \sum_{n=0}^{\infty} [(1-y) w]^n \\ &= \frac1{\sqrt{\pi}} \int_0^1 dy \, \frac{y^{-1/2} (1-y)^{-1/2}}{1-w (1-y)} \\ &= \frac{2}{\sqrt{\pi}} \int_0^1 dy \frac{(1-y^2)^{-1/2}}{1-w (1-y^2)} \\ &= \frac1{2 \sqrt{\pi}} \int_0^{2 \pi} \frac{d\theta}{1-w \sin^2{\theta}} \end{align}$$

where we assume that $|w| \lt 1$. That last integral may be performed any number of ways, e.g., extension to the complex plane and the residue theorem. The result is $2 \pi/\sqrt{1-w}$. Thus,

$$S = \sqrt{\frac{\pi}{1+\frac1{x}}} = \sqrt{\frac{\pi x}{x+1}} $$


Let's illustrate how to do that last integral.

$$\int_0^{2 \pi} \frac{d\theta}{1-w \sin^2{\theta}} = 2 \int_0^{\pi} \frac{d\theta}{1-w \sin^2{\theta}} = 2 \int_0^{\pi} \frac{d\theta}{1-w/2 + (w/2) \cos{2 \theta}} = \int_0^{2 \pi}\frac{d\theta}{1-w/2+(w/2) \cos{\theta}}$$

The above manipulations serve to show how to reduce a potentially messy problem into one a lot less messy. In this case, we have reduced the number of poles in the complex plane from four to two.

Now express as a complex integral using $z=e^{i \theta}$; the integral is equal to

$$-i 2 \oint_{|z|=1} \frac{dz}{(w/2) z^2 + (2-w) z+(w/2)} $$

The poles of the integrand are at $z_{\pm}=[-(2-w) \pm 2 \sqrt{1-w}]/w$, and the only pole inside the unit circle is $z_+$. Thus, by the residue theorem, the integral is equal to $i 2 \pi$ times the residue at that pole, the residue being equal to $1/(2 \sqrt{1-w})$. Thus the integral is equal to $2 \pi/\sqrt{1-w}$ as asserted.

  • $\begingroup$ well done! (+1) nice use of the beta integral $\endgroup$ – tired Feb 15 '17 at 21:47
  • $\begingroup$ Ron, nice use of the Beta function and successive substitutions. (+1) And nice to see you're still here! -Mark $\endgroup$ – Mark Viola Feb 15 '17 at 21:48
  • $\begingroup$ @Dr.MV: Thanks Mark. I never left. I still lurk but I am hardly in a place to keep my former pace. Nice to see you guys producing quality answers. $\endgroup$ – Ron Gordon Feb 15 '17 at 21:49
  • $\begingroup$ Thanks Ron ... still trying to fill your large shoes from time to time. $\endgroup$ – Mark Viola Feb 15 '17 at 21:50

$$ \sum_{n=0}^\infty \left(-\frac{1}{x}\right)^n\frac{1}{n!}\frac{1}{4^n}\frac{(2n)!}{n!}\sqrt{\pi} = \sum_{n=0}^\infty \left(-\frac{1}{4x}\right)^n\frac{(2n)!}{(n!)^2}\sqrt{\pi} = \sum_{n=0}^\infty \left(-\frac{1}{4x}\right)^n\left(\matrix{2n\\n}\right)\sqrt{\pi} $$ the final is of the form $$ \sum_{k=0}^\infty \left(\matrix{2k\\k}\right)z^k = \frac{1}{\sqrt{1-4z}}\;\;\text{iff}\;\; |z| <1/4 $$ (see wiki)

if we have $$ \left|\frac{1}{-4x}\right| =\left|\frac{1}{4x}\right| < \frac{1}{4} $$ then we have $$ \sum_{n=0}^\infty \left(-\frac{1}{4x}\right)^n\left(\matrix{2n\\n}\right)\sqrt{\pi} = \frac{1}{\sqrt{1-4\frac{1}{-4x}}}\sqrt{\pi}= \sqrt{\frac{x\pi}{1+x}} $$

  • $\begingroup$ @Dr.MV Cheers Mark! $\endgroup$ – Chinny84 Feb 15 '17 at 21:58

$\newcommand{\bbx}[1]{\,\bbox[8px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$ \begin{align} &\sum_{n = 0}^{\infty}\pars{-\,{1 \over x}}^{n}\, {\Gamma\pars{\bracks{2n + 1}/2}\over n!} = \pars{-\,{1 \over 2}}!\sum_{n = 0}^{\infty} {n - 1/2 \choose n}\pars{-\,{1 \over x}}^{n} \\[5mm] = &\ \root{\pi}\sum_{n = 0}^{\infty}\underbrace{\bracks{{- 1/2 \choose n}\pars{-1}^{n}}}_{\ds{\underbrace{=\ {n - 1/2 \choose n}}_{\ds{\mbox{Negating Property}}}}}\ \pars{-\,{1 \over x}}^{n} = \root{\pi}\sum_{n = 0}^{\infty}{-1/2 \choose n}\pars{1 \over x}^{n} \\[5mm] = &\ \root{\pi}\pars{1 + {1 \over x}}^{-1/2} = \bbx{\ds{\root{\pi x \over x + 1}}}\,,\qquad\qquad \verts{x} > 1. \end{align}


We may also prove this by working backwards from the integral $\int_0^\infty\frac{t^{x-1}}{(1+t)^{x+y}}dt=\frac{\Gamma(x)\Gamma(y)}{\Gamma(x+y)}$ and applying Ramanujan's master theorem.

We start with the following integral: $$\begin{align*} \int_0^\infty\sqrt{\frac{\pi/t}{1+1/t}}t^{s-1}dt &=\sqrt{\pi}\int_0^\infty\frac{u^{-s-1/2}}{(1+u)^{1/2}}du,\;\;t=u^{-1} \\ &=\sqrt{\pi}\int_0^\infty\frac{u^{1/2-s-1}}{(1+u)^{1/2-s+s}}du \\ &=\Gamma(1/2-s)\Gamma(s),\;\;0<\Re [s]<1/2. \end{align*}$$

Which implies that $\phi(s)=\Gamma(1/2+s)$. So we then have

$$\begin{align*}\sqrt{\frac{\pi/t}{1+1/t}}&=\sum_{n=0}^\infty\frac{\phi(n)}{n!}(-t)^n\\ &=\sum_{n=0}^\infty\frac{\Gamma(1/2+n)}{n!}(-t)^n,\;\;|t|<1. \end{align*} $$

Replacing $t$ with $1/t$ yields your sum.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.